MANAJEMEN PEMBELAJARAN BERBASIS SPIRITUALITAS DAN RELIGIUSITAS KRISTIANI DALAM RANGKA MENINGKATKAN MUTU PENDIDIKAN DI SMP BHAKTI MULIA WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The purpose of  research  is to describe how the christian spirituality and religiousity play role, influence, and base for  educational quality in Junior High School. These christian spirituality and religiousity are exist in every aspects in educational of management are included as  planning, organizing, actuating, and evaluating.This  research used the qualitative research  and  qualitative metodology. One of the characteristic of this research model was that the research was done in  restricted population. In other hand, this research tried to find a meaning behind the fenomena. The collecting of field data has gotten through field observation, survey, interview, and documents collection. This research was done in SMP Bhakti Mulia Wonosobo. The data were analyzed by giving some meanings and  researcher created a narrative writing and made a conclution.The results of this research pointed out about the christian spiritualiy and religiosity. It was a  spirit or a  soul or an energy that appear in some educational ideas in teacher’s meeting  community context in SMP Bhakti Mulia Wonosobo. Christian spiritualiy and religiousity influence student’s charracter building as well. The christian spirituality and religiousity aspects were exist through planning, organizing, actuating, and evaluating. All of those were actuated by teachers and staffs. They were encouraged by spirit of love (Agape) and worship as core of the christian’s faith. Ideologically, all christ’s disiples has to love and serve their neighbor every time and everywhere. The conclution also pointed out to the increasing of educational quality was  not only seen through student’s achievement in the main subject in Junior High School’s  curriculum, but also it was seen through in the performance of student’s charracter building.